Analysis of Historical Stages of Urban Planning In Khiva - Ulugbekovich, Ruzmetov Shohruh (European Journal of Life Safety and Stability (2660-9630), 2022)
In this article we will consider the stages of formation of Khiva urban planning and architecture, as well as the factors that influenced urban planning in different periods. We analyze the period of development and decline of the city in the Achaemenid period, the period of the Kushans, the period of the Khorezmshahs, the end of the XVIII century - the XIX century and the Soviet era.